THE E-HEALTH SYSTEMS IN POLAND - Zdzisław PÓLKOWSKI; Małgorzata WALCZAK (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
Information Technologies are disruptive technologies that have caused major changes in health system in Poland. Current digital economy is driven by modern information and new IT tools, which offer hospitals, doctors and patient access to any type of information, regardless of its form of existence, storage type or geographical location. These tools encourage the development of new activities, health services. The purpose of this article is to analyze the the current state of development of e-services in Poland in the context of nowadays health system. In the first part of the paper, the authors present various programmes, which enable the access to the medical services and patients’ data online. The next part of the paper is devoted to examining the technical aspects of the said programmes and presenting their advantages as well as the areas which might be improved.The last part of the work will be focused on the websites of the selected health institutions. According to the authors, WWW services provide much information on how the process of computer systems are being implemented, what data the services include and the capacity of the equipment as well as the software, human resources and the knowledge in this sphere. Moreover this section highlights the latest trends in e-health with particular emphasis on aspects such as the use of private and public cloud computer and t heir integration with web sites of health institutions. This study brings its contribution to the understanding of the change of health system in Poland behavior by using a new perspective e-health systems and IT tools above by doctors, officers and patients.